Complementary Methods of Processing diS-C3(3) Fluorescence Spectra Used for Monitoring the Plasma Membrane Potential of Yeast: Their Pros and Cons - Plášek, Jaromír; Gášková, Dana (Journal of fluorescence, 2014)
Carbocyanine dye diS-C3(3) was repeatedly employed in monitoring the plasma membrane potential of yeast and other living cells. Four methods of measuring and evaluating probe fluorescence signal were used in different studies, based on following fluorescence parameters: fluorescence intensity emitted within a certain spectral interval, F(580)/F(560) fluorescence emission ratio, wavelength of emission spectrum maximum, and the ratio of respective fluorescence intensities corresponding to the diS-C3(3) bound to cytosolic macromolecules and remaining dissolved in the aqueous cell medium (i.e., unbound, or free). Here we show that data corresponding to the three latter spectral assessments of diS-C3(3) accumulation in cells is mutually convertible, which means that their alternative use cannot lead to ambiguities in the interpretation of the results of biological experiments. On the other hand, experiments based on the effortless measurements of fluorescence intensities should be interpreted cautiously because controversial results can be obtained, depending on the particular choice of cell-to-dye concentration ratio and emission wavelength.
Keywords: fluorescenční barviva; Saccharomyces cerevisiae; Spectrometry, Fluorescence; membránové potenciály; karbocyaniny; fluorescenční spektrometrie; Carbocyanines; Membrane Potentials; Fluorescent Dyes